Tino Rangatiratanga and Well-being: Māori Self Determination in the Face of Covid-19 - Te One, Annie; Clifford, Carrie (Frontiers in Sociology, 2021)
The New Zealand government has been globally praised for its response to Covid-19. Despite the global accolades, little attention has been given to the swift and innovative Māori response to Covid-19. This paper will detail some of this rapid Māori response to Covid-19 in Aotearoa New Zealand and argue the response can be understood as key examples of Māori exercising tino rangatiratanga (self-determination), independent of the government’s measures and policies. We suggest that this exploration of tino rangatiratanga during Covid-19 demonstrates central aspects of Māori well-being that move beyond a government focus on statistics as the key measure of well-being and how tikanga Māori (Māori values) are being used to develop successful responses to the global pandemic.